The construction of knowledge in post-colonial societies: Listening to the life histories of three generations in Mozambique - Carvalho, X. (SRHE Newer Researchers Conference, 2014)
This research is focused on the narratives of three generations of Mozambican students after the independence of the country in 1975 to the present day. The generational narratives are contextualized within the meta-narratives of each political and ideological period in Mozambique crossed by a common factor: the Civil War from 1976 until 1992. The research question that links this study is: How is knowledge constructed in the education system in Post-Colonial society, namely over three generations in Mozambique, and how does this impact upon their personal and social identity? To understand the two dimensions of this research (i.e. education and identity) a qualitative methodology was used, particularly an ethnographic and narrative approach, collecting 18 life histories of three generations of Mozambican students that did or are still doing degrees in higher education. The data analysis of the life histories collected in 2013, as well as the ethnographic techniques used (i.e. direct observation, participant observation and fieldwork diary reflections), have the purpose of understanding how the three generations define their multiple identities, and if education experiences changed their personal and social identity. In the end, the idea is to understand the links between education and identity in post-colonial Mozambique.